Clinical characteristics and comorbidities in adult-onset Still’s disease using a large US administrative claims database - Lenert, Aleksander (Rheumatology (Oxford), 2020)
OBJECTIVES: We aimed to describe clinical characteristics, treatment patterns and major comorbidities of a US-based adult-onset Still’s disease (AOSD) cohort. METHODS: Administrative claims data from Truven MarketScan were collected from 2009 to 2015. An AOSD case was defined as ≥1 M06.1 International Classification of Diseases 10th revision (ICD-10) medical claim code. We extracted data for the AOSD cohort (n = 106) and 1:5 matched controls (n = 530) without AOSD. Outcomes of interest and a novel claims-based set of Yamaguchi criteria were identified by relevant ICD 9th revision (ICD-9) and ICD-10 codes. Bivariate descriptive analyses were conducted on all variables. Comorbidity rates and rate ratios were calculated in AOSD cases and matched controls. Statistical significance of cohort differences was determined to compare AOSD cases and matched controls. RESULTS: The AOSD cohort, with a mean age of 43.08 (standard deviation, s.d. 13.9) years and with female predominance (68.9%) was observed over a mean of 750.12 (637.6) days. A total of 35.9% of AOSD patients fulfilled claims-based Yamaguchi criteria compared with 0.4% matched controls (P< 0.05). We identified severe AOSD-related complications, including macrophage activation syndrome (4.7%) and acute respiratory distress syndrome (12.3%). Treatment commonly involved systemic glucocorticoids (62.2%), MTX (51%) and anakinra (24.5%). Compared with matched controls, serious infections were significantly increased (rate ratio 2.58, 95% CI: 1.53, 4.37, P = 0.0004), while hyperlipidaemia (0.54, 95% CI: 0.35, 0.85; P = 0.008) and obesity (0.30, 95% CI: 0.15, 0.62; P = 0.001) were significantly decreased in AOSD patients. CONCLUSION: We characterized a first US-based AOSD cohort using a large national administrative claims database, and identified key complications, treatments and comorbidities.